Why corporate restructuring and downsizing efforts often fail - Trevor, Charles O. (Henry Stewart Talks, 2014)
Layoffs, downsizing & restructuring, Downsizing context, Why does downsizing failure occur: Questionable decision-making on whether and how to downsize, Beyond questionable decision-making, Effects on “survivors”: Voluntary turnover & Job performance-related factors, Effects on “victims”, Recommendations